Variation in orosensation and liking of sampled foods with thermal tasting phenotype. Issue 1 (December 2016) - Pickering, Gary; Lucas, Sarah; Gaudette, Nicole
Abstract Background Flavour is a key driver of liking, purchase behaviour and consumption of food and beverages. Determining how individuals differ in their perception of flavour is important to fully understanding dietary choices and habitual diet-related health outcomes. Thermal tasting—the capacity to experience a phantom taste when small areas of the tongue are rapidly heated or cooled—associates with greater orosensory acuity for tastants in aqueous solutions. This study sought to extend this finding and establish whether thermal-taster status also associates with the perceived intensities of oral sensations elicited by sampled food. Twenty-five thermal tasters (TTs) and 19 thermal non-tasters (TnTs) scored liking (generalized degree of liking scale) and the intensity (generalized visual analogue scale) of the dominant orosensations elicited by 20 food and beverage items in duplicate using a randomized complete block design. Results Multiple analysis of variance (MANOVA) showed that overall, TTs rated the intensity of orosensory food groups higher than did TnTs, although this was significant only for foods that were predominantlybitter -eliciting (ANOVA). Overall liking scores approached significance (MANOVA) but differed between TTs and TnTs only for thegrainy orosensory food grouping (ANOVA). Conclusions These findings are discussed in the context of diet-related health outcomes and directions for further research concerned with taste phenotypes, flavour perception and consumption behaviours.